On Some Aspects of the Participation of Experts and Specialists in Criminal Proceedings in the Republic of Kazakhstan - K. K. Seitenov; A. Z. Saken (Теория и практика судебной экспертизы, 2024)
The article considers particular reasons for the start of a pre-trial investigation, which are associated with the participation of persons having specialized knowledge in the proceedings.By using a number of methods of cognition of the circumstances of reality, the authors identify the issues that require resolution at the intersectoral level. Among the problematic aspects that cause the violation of citizens’ rights, there is a premature start of the pre-trial investigation, which is also due to the inconsistency and unreliability of the conclusions of experts and specialists involved both before and during the pre-trial investigation.To improve the studied sphere of public relations, proposals are made on overcoming of organizational and legal shortcomings of operational investigative activities, reasons for starting a pre-trial investigation, as well as filling the gaps in the current legislation, in terms of bringing experts and specialists to administrative and criminal responsibility.